If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14x + -153 = -7x + -90 Reorder the terms: -153 + -14x = -7x + -90 Reorder the terms: -153 + -14x = -90 + -7x Solving -153 + -14x = -90 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -153 + -14x + 7x = -90 + -7x + 7x Combine like terms: -14x + 7x = -7x -153 + -7x = -90 + -7x + 7x Combine like terms: -7x + 7x = 0 -153 + -7x = -90 + 0 -153 + -7x = -90 Add '153' to each side of the equation. -153 + 153 + -7x = -90 + 153 Combine like terms: -153 + 153 = 0 0 + -7x = -90 + 153 -7x = -90 + 153 Combine like terms: -90 + 153 = 63 -7x = 63 Divide each side by '-7'. x = -9 Simplifying x = -9
| -r/3=-100 | | -14+135=-7x+79 | | Y-z=x-y | | 17x+60=9x+36 | | 5/24=10/g | | 4/9a=1/9a-5/6 | | 5n-6=-106 | | 14x-76=8x-40 | | -6x-28=-3x-16 | | 0.09xX=72.44 | | -18x-83=-12x-47 | | -8x+32=-5x+17 | | h-6.5=15.2 | | 4y-3x=-84 | | -5x+26=-3x+16 | | 52=w/4 | | 9x+36=6x+18 | | F(x)=-1(x+1)(x-7) | | 3x+37=11.25 | | -18x+31=-12x+19 | | cos70=14/x | | 48-4x=7x | | 2-(x+1)=2x-11 | | 6(3x-2)=3-2(4x+1) | | -9x+9=-6x+6 | | m/2=27 | | 7x+4=7(8)+4 | | 6(w-2)=-7w-25 | | 19x-79=12x-44 | | 8(-2x+3)=32 | | 80-2x=50 | | x-.3x=38000 |